Identification of Interlayer Distribution of Marine Sandstone Based on Four-dimensional Well Test Technology. Issue 2 (May 2021) - Li, Ke; Li, Yao; Zhang, Peng; Wang, Kai; Tang, Chenyang; Tang, Jing
Abstract: Reservoir compartment is one of the important influence factors of fluid flow in the reservoir, and it is of great significance to carry out the research on reservoir compartment understanding and characterization for the research and development of residual oil distribution in the middle and late stages of an oil field. However, how the reservoir compartment is distributed, the current method is mainly throughout open heads, rock hearts, logging, and other information to explain, but this method is limited to blocks. Because of this problem, we use the four-dimensional test well method to calculate the distribution of the oil deposit formation coefficient based on the test well pressure data, and then use pressure denoising technology to make the data smoother, and the resulting two-pair curve plate is clearer, the layout can be used to explain the distribution of the compartments in the work area. This method requires only test pressure data and is suitable for multiple workspaces. This is of great guiding significance to the development of sea-phase sandstone inter-layer reservoirs.